2019
DOI: 10.1152/ajpregu.00084.2019
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral fatigue during severe-intensity single-leg exercise: influence of acute acetaminophen ingestion

Abstract: Exhaustive single-leg exercise has been suggested to reduce time to task failure (Tlim) during subsequent exercise in the contralateral leg by exacerbating central fatigue development. We investigated the influence of acetaminophen (ACT), an analgesic that may blunt central fatigue development, on Tlim during single-leg exercise completed with and without prior fatiguing exercise of the contralateral leg. Fourteen recreationally active men performed single-leg severe-intensity knee-extensor exercise to Tlim on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
2
8
1
Order By: Relevance
“…The correlations between TTF and the rate of change in effort perception across both conditions suggest that this increased effort perception induced by the HG exercise caused faster attainment of maximal effort. Our results support previous observations in both single limb and whole‐body exercise, demonstrating increased effort perception following prior remote exercise independent of concomitant changes in the neuromuscular function (Amann et al., 2013; Johnson et al., 2015; Morgan et al., 2019). The results of the present study also parallel those observed following prior cognitive tasks (Pageaux et al., 2013; Pageaux, Marcora, Rozand, & Lepers, 2015) which may support the proposal that prior cognitive activity and remote motor exercise increase effort and limit subsequent motor performance through shared processes within the brain (Pageaux & Lepers, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlations between TTF and the rate of change in effort perception across both conditions suggest that this increased effort perception induced by the HG exercise caused faster attainment of maximal effort. Our results support previous observations in both single limb and whole‐body exercise, demonstrating increased effort perception following prior remote exercise independent of concomitant changes in the neuromuscular function (Amann et al., 2013; Johnson et al., 2015; Morgan et al., 2019). The results of the present study also parallel those observed following prior cognitive tasks (Pageaux et al., 2013; Pageaux, Marcora, Rozand, & Lepers, 2015) which may support the proposal that prior cognitive activity and remote motor exercise increase effort and limit subsequent motor performance through shared processes within the brain (Pageaux & Lepers, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…These paradigms may thus offer a means of investigating the perceptual regulation of exercise in isolation. For example, prior motor activity has been shown to reduce endurance performance in remote non‐activated muscles (Amann et al., 2013; Bangsbo, Madsen, Kiens, & Richter, 1996; Johnson, Sharpe, Williams, & Hannah, 2015; Morgan et al., 2019; Nordsborg et al., 2003), increasing the perception of exertion or effort during the endurance task independent of observable changes in the neuromuscular function (Amann et al., 2013; Johnson et al., 2015; Morgan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…NLMF refers to deficits of maximal force output in any contralateral or ipsilateral, homologous or heterologous, non-exercised muscles (Halperin et al, 2015, Miller et al, 2019, Ye et al, 2018, whereas crossover fatigue is a subgroup of NLMF and specifically describes the impairment of a contralateral, homologous, non-exercised muscle (Doix et al, 2018;Halperin et al, 2015;Martin and Rattey, 2007). Contrary to these concepts however, numerous studies failed to show NLMF effects (Aboodarda et al, 2019;Andrews et al, 2016;Doix et al, 2018;Grabiner and Owings, 1999;Hamilton and Behm, 2017;Kennedy et al, 2015;Morgan et al, 2019;Prieske et al, 2017). Indeed, there are a number of inconsistencies and gaps in the NLMF literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the final number of studies included was 52[118][119][120][121][122][123][124][125][126][127][128][129]: citations for studies not otherwise referenced in the manuscript but included in the data extraction table]. Details of the search and inclusion process are shown in the flow chart (figure 1).…”
mentioning
confidence: 99%